2013
DOI: 10.2503/jjshs1.82.234
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Dormancy and Early Flowering Ability in Lilium longiflorum and L. formosanum Populations in the Ryukyu Archipelago and Taiwan

Abstract: Variations in the dormancy and early flowering ability of seedlings of four populations of Lilium longiflorum, Yaku Shima (LYA), Kikai Jima (LKI), and Ishigaki Jima (LIS) in the Ryukyu Archipelago, Japan and Pitouchiao (LPI), Taiwan, and two populations of L. formosanum, Wulai (FWU), Taiwan and a domesticated Fukuoka population (FFU), Japan were investigated. Seedlings of each population were grown at 15°C for five months. They were then transplanted into an experimental open field for two years or at 15, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
1
4
0
1
Order By: Relevance
“…We reported that temperature is the main factor to distinguish the degree of dormancy in L. longiflorum and L. formosanum populations of the Ryukyu Archipelago (Mojtahedi et al, 2011(Mojtahedi et al, , 2012. In the present study, it was shown that growth continues in all populations at low temperature (15°C), while the growth rate in winter is less than in summer.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…We reported that temperature is the main factor to distinguish the degree of dormancy in L. longiflorum and L. formosanum populations of the Ryukyu Archipelago (Mojtahedi et al, 2011(Mojtahedi et al, , 2012. In the present study, it was shown that growth continues in all populations at low temperature (15°C), while the growth rate in winter is less than in summer.…”
Section: Discussionsupporting
confidence: 46%
“…We found that one-year-old seedlings of L. formosanum and L. longiflorum populations growing in the southern part of the Ryukyu Aarchipelago showed no or weak dormancy and keep growing even at high temperature (25 and 30°C) in July and August, while northern populations of L. longiflorum stopped leaf development when the temperature reached to 25°C in the middle of June and remained deep dormant state until the end of the following January (Mojtahedi et al, 2011(Mojtahedi et al, , 2012. In those experiments, it was suggested that dormancy in northern populations was induced by high summer temperature, and the effect of temperature was confirmed as an important factor for the differentiation of degrees of dormancy in L. longiflorum populations over the geographic gradient of the Ryukyu Archipelago (Mojtahedi et al, 2011(Mojtahedi et al, , 2012.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, the most important floral induction factors in garlic should be variety, bulb storage duration and temperature, and photoperiod and growth temperature (Pooler and Simon, 1993). Chilling treatment during bulb storage has been researched significantly on Allium and Lilium (Le Nard and De Hertogh, 1993;Bandara et al, 2000;Khokhar et al, 2007;Lee et al, 2007Lee et al, , 2008Mojtahedi et al, 2012Mojtahedi et al, , 2013Lucidos et al, 2014), but chilling treatment on bulbs as a substitute for plant vernalization has rarely been reported. The results of Karaguzel and Baktir (2013) indicate that cold treatments and their durations had significant effects on the flower stem length, flower stem diameter and flowering time of Allium robertianum Kolmann; the best results were obtained from bulbs stored at 10 • C for a 30-day period in a heated glasshouse, while the earliest flowering was observed in bulbs stored at 5 • C for 60 days in the glasshouse.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the optimum conditions to fully vernalize onion cultivars were under low-temperature (-11 • C) treatments for 7-90 days (Khokhar et al, 2007). The role of lowtemperature storage for growth and development in other bulbs has also been well demonstrated (Mojtahedi et al, 2012(Mojtahedi et al, , 2013. Tulip (Tulipa gesneriana) bulbs require a low-temperature treatment (4-5 • C) for shoot elongation and flower formation (Le Nard and De Hertogh, 1993).…”
Section: Introductionmentioning
confidence: 99%